Assessment of sedimentation in Tri An reservoir by nuclear technique, geological analyses and GIS - Tan, Mai Thanh; Thuan, Dinh Van; Ha, Vu Van; Tan, Nguyen Trong; Luong, Le Duc; Ha, Trinh Thi Thanh; Tao, Nguyan Van; Quan, Nguyen Cong (Vietnam Journal of Earth Sciences, 2014)
Assessment of sedimentation in Tri An reservoir herein is based on sounding data and sedimentary thickness data,obtained by nuclear technique and geological analyses of samples taken from the reservoir. From these data, using GIStools, the digital depth models and sediment thickness maps are built for the years of 1987 (moment of putting reservoirin operation), 2010 (the present, moment of fieldwork for sounding and sampling), 2020 (10 years in future) and 2060 (50years in future). The conclusion is made from these models, maps and their data extractions as follows:- During the past 23 years, from 1987 to 2010, Tri An has been deposited with a thickness approximately of 12 cmin average and 132 cm maximum. The sedimentation occurs largely in the upper part (the northeast) of the reservoir,especially in the area near the position where the Dong Nai and La Nga River flows in.- In the next 10 years (2020) the thickness would reach averagely 17 cm and maximally 189 cm. The area withthickness over 75 cm occupies only 3% of total lake.- In the next 50 years (2060) the average and maximal thickness would respectively be 38 cm and 417 cm. Thethickness over 150 cm accounts for 3% of total area and those over 200 cm occupies only 1% total.- Sedimentation has led to reduced reservoir volume (in both inactive and active) affecting the operation activity.However, this effect is negligible because the active volumes in 2020 and 2060 would respectively remain 98.8% and97.0% of its the initial volume.Despite some limitations due to insufficient input data and calculation errors, the assessment is still acceptable. References Phan Sơn Hải, 2004. Khảo sát bồi lắng lònghồ thủy điện Trị An bằng kỹ thuật hạt nhân. Thôngtin KHCNHN số 2. Nguyễn Văn Phổ và Nguyễn Trung Minh, 1995. Một số kết quả tính toán tốc độ bồi lắng hồ chứa Thác Bà bằng phương pháp đồng vị môi trường. Viện Thông tin tư liệu địa chất “thông tin khoa học kỹ thuật địa chất”. Tập IV, số 2-4, tr.46-56. Hà Nội. Nguyễn Văn Phổ và Nguyễn Trung Minh, 1996. Một số kết quả tính toán tốc độ bồi lắng hồchứa Thác Bà bằng phương pháp đồng vị môitrường. Thông tin Khoa học kỹ thuật địa chất,số 2-4. Nguyễn Văn Phổ, Hoàng Thị Tuyết Nga, Nguyễn Trung Minh, 1996. Ứng dụng phương pháp đồng vị môi trường trong nghiên cứu bồi lắng một số hồ chứa khu vực Điện Biên. Thông tin Khoa học kỹ thuật địa chất, số 3-5. Nguyễn Văn Phổ, 1997. Phương pháp nghiên cứu bồi lắng ven biển và hồ chứa bằng đồng vị phóng xạ chì 210. Thông báo khoa học: Các khoa học Tự nhiên (Đại học Quốc gia Hà Nội), số 4, trang 72-78. Nguyễn Văn Phổ và Hoàng Tuyết Nga, 1997. Kết quả nghiên cứu bồi lắng lòng hồ ở một số vùng miền núi phía Bắc bằng phương pháp đồng vị chì 210. Thông báo khoa học: Các khoa học tự nhiên (Đại học Quốc gia Hà Nội), số 4, tr.79-85. Nguyễn Văn Phổ, 1998. Khả năng ứng dụng phương pháp đồng vị chì 210 trong nghiên cứu bồi lắng hồ chứa ở Việt Nam. Hội nghị Khoa học Đại học Mỏ - Địa chất lần thứ 13, số 3, tr.165-168. Lương Văn Thanh, 2006. Nghiên cứu đánh giá mức độ bồi lắng hồ Trị An phục vụ công tác bảo vệ an toàn hồ chứa. Tạp chí Nông nghiệp và Phát triển Nông thôn, số 18, tr.91-94.